2017
DOI: 10.1007/978-94-024-1079-2_84
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Function of Taurine on Bone Metabolism in Alcohol-Fed OVX Rat Model

Abstract: The present study investigates the effects of taurine on bone markers and bone mineral density (BMD) in alcohol-fed ovariectomized (OVX) rat model. We divided twenty four rats into Sham and OVX groups. These two groups were thereafter subdivided into two groups: control and experimental diet containing 2 g/kg of taurine. BMD and bone mineral content (BMC) were estimated by PIXImus. As bone markers, we measured serum calcium, phosphorus, ALP activity, osteocalcin and urine calcium, phosphorus and DPD crosslinks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Also, recent metabolomics studies reported that the amino acids including glutamine [ 8 ], tryptophan [ 9 ], and cystine [ 10 ] were associated with BMD in postmenopausal women of East Asian. Of these identified BMD-related amino acids in our study, GABA [ 28 ], cysteine [ 29 ], taurine [ 30 ], and glutamic acid [ 31 ] have shown some evidence for their potential roles in bone metabolism by in vitro and/or in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, recent metabolomics studies reported that the amino acids including glutamine [ 8 ], tryptophan [ 9 ], and cystine [ 10 ] were associated with BMD in postmenopausal women of East Asian. Of these identified BMD-related amino acids in our study, GABA [ 28 ], cysteine [ 29 ], taurine [ 30 ], and glutamic acid [ 31 ] have shown some evidence for their potential roles in bone metabolism by in vitro and/or in vivo studies.…”
Section: Discussionmentioning
confidence: 97%
“…Taurine supplementation has been linked with increased femur BMD in OVX rats [ 30 ]. However, another study did not observe any difference in femur bone mineral content between two groups of OVX rats fed with calcium deficient diet with or without taurine supplementation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to hypocalcemia in menopause, bone mineral density decreases, and the risk of fracture increases. It has been shown that taurine has a positive effect on bone mineral density and content and increases serum Ca and phosphate levels in ovariectomy-induced osteoporotic rats [ 13 ]. Taurine supplementation has been shown to significantly reduce osteocalcin levels in B12-deficient infant rats [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It reduces bone loss by inhibiting osteoclastogenesis [ 11 , 12 ]. Animal experiments have supported that taurine supplementation reduces alveolar bone resorption [ 8 ], prevents bone loss in ovariectomized rats [ 6 , 11 , 13 ], and has anabolic effects on bone health in growing rats [ 9 , 12 ], without significant side effects or toxicity. Oral taurine tablets have been reported to reduce postoperative oxidative stress in elderly patients with hip fractures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 2 % taurine in control diet increases femur BMC per weight in growing rats (Choi and Seo 2013). Taurine supplemented diets may have positive results on bone metabolism in alcohol-fed OVX rat model (Choi et al 2017). According Vol.…”
mentioning
confidence: 99%